The static and fatigue behavior of low profile precast concrete sleepers - Goodhead, Andrew H (Department of Civil Engineering, 2020)
Low Profile precast concrete sleepers have the same vertical dimension as traditional wooden sleepers and thus offer a promising alternative to replace wooden sleepers on tracks where maintaining vertical alignment is necessary. The structural response of Low Profile precast concrete sleepers was studied under static and fatigue loading regimes using a tuned finite element model and four point flexure laboratory tests. The fatigue tests were conducted by following the procedure specified in the Australian railway code (AS 1084.14-2012). The usefulness of the Australian code fatigue test was brought into question as the fatigue life of Low Profile sleepers far exceeded the 3 million load cycle specified by the code. This study concluded that Low Profile concrete sleepers have excessive fatigue resistance however the limiting design criteria for Low Profile sleepers should be governed by a serviceability approach in order to limit cracking and thus ensure an adequate durability life span.